Analisis Sarana dan Prasarana Olahraga di MI Masalikil Huda Tahunan Jepara - Khofiva, Khusnul; Efendi, Abdullah (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research is conducted based on the problems found regarding the condition of sports facilities and infrastructure that are still lacking. The aim of this research is to ascertain the availability and condition of sports facilities and infrastructure at MI Masalikil Huda Tahunan Jepara. The type of research used is qualitative descriptive research. The subjects of this study include the school principal, PJOK teachers, and students. The subject of this research is the sports facilities and infrastructure available at the school. The data collection techniques used in this research include interviews, observations, and documentation. Meanwhile, the data analysis technique applied uses the Miles and Huberman model, which includes the stages of data collection, data reduction, data presentation, and conclusion drawing. Based on the research findings, the availability of sports facilities and infrastructure at MI Masalikil Huda Tahunan Jepara still faces shortages and obstacles in meeting the needs for sports facilities and infrastructure for PJOK learning.